Biomarkers in acute kidney injury - Galvis, Nehomar Pajaro; Rico-Fontalvo, Jorge; Daza-Arnedo, Rodrigo; Cardona- Blanco, Maria Ximena; Abuabara-Franco, Emilio; Leal-Martínez, Victor; Cabrales-Juan , Jose; Correa- Guerrero, José; Bohórquez- Rivero, José; Sáenz-López, José; et al. (Journal of Clinical Nephrology, 2020)
Acute kidney injury is a common condition associated with high morbidity and short-term mortality. Its pathophysiology varies according to the numerous conditions associated with its genesis. Biomarkers allow detecting changes at the level of kidney function; therefore, they play an important role in the prevention, early diagnosis, therapeutic response and prognosis of acute kidney injury. The search for biomarkers for acute kidney injury began over 15 years ago; initially, only serum creatinine was available for diagnosis. However, throughout history, great advances have been made in research, which have allowed the finding of new biomarkers in order to improve the health and quality of life of patients. A narrative review of the literature is carried out on the basis of available scientific evidence to clarify the role and importance of biomarkers in the context of acute renal injury.